MENGUAK POTENSI SI KAYU API (DIOSPYROS SP. ) PENGHASIL RACUN IKAN ALAMI DARI HUTAN JEMBRANA BALI BARAT - Andila, P.S.; Peneng, I.N. (Buletin Udayana Mengabdi; Vol 16 No 3 (2017), 2018)
Kayu Api (Diospyros sp.) is one species in the group of ebony wood (Ebenaceae family) that live naturally in the protected forest area of West Bali, Jembrana Regency. This plant has potential as a natural fish poison but the information about the potential of Kayu Api has never been published before. The purpose of this study was to explore the potential of Kayu Api As natural fish poison and conduct comparative studies of Diospyros spp. potentially as natural fish poison. The research was conducted by exploration method, interviewing, and literature study. The results of this research indicate that leaf and fruit extracts of Kayu Api are used as natural fish poison by Jembrana local people. Some species of Diospyros spp. have also been reported as a plant producing natural fish poison.